Effect of CR and DAR on ROA in Automotive and Component Companies Listed on the IDX - Intan Triana Hartanti; Ruhadi Ruhadi; Anny Suryani (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The aim of this research is to know the effect of Current Ratio and Debt to Asset Ratio to Return on Assets on companies subsector of automotive and components listed on Indonesia Stock Exchange Period 2017-2021. The research method used is a quantitative descriptive method. This research used purposive sampling method and obtained 7 samples of companies in the automotive subsector and components listed on the Indonesia Stock Exchange Period 2017-2021. In this study the model and technique of data analysis used panel data regression approach. The selected panel data regression model is Random Effect Model. The results showed that Current Ratio partially had a negative and significant effect on Return on Assets and Debt to Assets Ratio partially had no significant effect on Return on Assets. While Current Ratio and Debt to Asset Ratio simultaneously had a significant effect on Return on Assets.